PENGARUH WAKTU PERENDAMAN LAPISAN TIO2 DALAM DYE EKSTRAK DAUN PACAR KUKU TERHADAP NILAI EFISIENSI DSSC - Israyanti, Israyanti; Iswadi, Iswadi; Hernawati, Hernawati (Universitas Islam Negeri Alauddin Makassar, 2019)
This study is about Dye Sensitized Solar Cell (DSSC) which aims to determine the absorbance value of henna leaf extract (Lawsonia Inermis L) as a sensitizer in DSSC and find out how the effect of immersion time of TiO2 layer on the efficiency value produced. The method used to make the extract is maceration and to doping TiO2 using the doctor blade method with an area of 1.5x1.5 cm. In this study UV-Vis testing was carried out to determine the absorbance value of dye henna leaf extract, current and voltage testing to determine the current and voltage values obtained from cells and SEM tests to determine the surface structure of TiO2 layers. The absorbance value of the nail extract leaf extract is based on the results of the UV Vis test which is 0.077 which is located in an area with a wavelength of 663 nm. For the TiO2 coating immersion time obtained the lowest efficiency value of cells with immersion of TiO2 layer for 1 hour which is 0.0038%, then immersion of TiO2 layer for 12 hours obtained efficiency value 0.0056% and soaking TiO2 layer for 24 hours obtained efficiency value 0.0083%.